STRENGTHENING OF SUBSTATE ACTORS IN COMPARATIVE ADVANTAGE OF SIJORI (SINGAPORE-JOHOR-RIAU ISLANDS) BORDER AREAS COLABORATION - Fitrisia Munir; Yanyan Mochamad. Yani; Siwage Dharma Negara; R. Widya Setiabudi Sumadinata (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this article is to examine another actor’s role in enhancing the comparative advantage of the border area, particularly for the Riau Islands, as part of international border area in SIJORI collaboration. Based on a review of the literature, the data were derived from a basic random-samples survey of local populations and immigrants using a research qualitative method approach. The motivations of this study were very interesting about Sijori collaborations and used the penta helix concept, which is becoming increasingly important in the process of competitive advantage. The old model of state-business cooperation is no longer a determining factor in global success. The results show that the importance of regional collaborations with sub-state actors, such as academic research collaborations with local governments, culture, and business between states, all of which need to contribute to border sustainability development. The researcher observed a high need for empowered border communities as members of the international community through sub-state actor cooperation. This is because the performance of the Riau Islands is below average when compared to other border states, so policies to strengthen the role of substate actors should be prioritized in border planning by local decision-makers and destination managers.